Level of coping with stressors in parents of epileptic children - T Taghavi Larijani; N.D Sharifi; A Mehran; Sh Nazari (Tehran University of Medical Sciences, 2006)
Background & Aim: Epilepsy as the most important chronic neurological disease affects on child and his/her family therefore it can lead to occur some stresses in family particularly in parents. This study has been done to determine ideas of parents with epileptic children about stressors and their coping with this agent in those who come to the optional therapeutic centers in Tehran. Methods & Materials: This is a descriptive-analytical research which 400 parents with epileptic children were selected based on aim. The method of collecting data was by questionnaire for literate persons and by interview for illiterates whose research tool was questionnaire. The questionnaire was prepared in three parts (demographic information's, stressors questions, and coping questions for parents with epileptic children. The data was collected in one stage and analyzed with SPSS software. To analyze the data, descriptive and inferential statistical methods (t-test, analyze variance) have been used. Results: Statistical analysis showed that there is significant differences in stress between parents (p=0.001). The most percentage (86%) of fathers in comparison mothers (81.9%) have moderate level of stress and least percentage (5.4%) fathers and (4.4%) of mothers have low level of stress. The level of stress in parents showed significant correlation with personal variables. Most percentage (69%) of fathers and mothers (66.1%) have low-moderate level of coping and it has significant correlation with some personal variables. The analyze variance test showed that there was significant and converse relationship between stress and coping in parents with epileptic children and increasing stress lead to decrease coping. Conclusion: The results of this study have been shown that the stress in father of epileptic children is more that mothers however there is no significant differences in the level of coping.